Human Papillomavirus vaccination clinical decision support for young adults in an upper midwestern healthcare system: a clinic cluster-randomized control trial - Melissa L. Harry; Stephen E. Asche; Laura A. Freitag; JoAnn M. Sperl-Hillen; Daniel M. Saman; Heidi L. Ekstrom; Ella A. Chrenka; Anjali R. Truitt; Clayton I. Allen; Patrick J. O’Connor; Steven P. Dehmer; Joseph A. Bianco; et al. (Human Vaccines & Immunotherapeutics, 2022)
Introduction Human papillomavirus (HPV) vaccination rates are low in young adults. Clinical decision support (CDS) in primary care may increase HPV vaccination. We tested the treatment effect of algorithm-driven, web-based, and electronic health record-linked CDS with or without shared decision-making tools (SDMT) on HPV vaccination rates compared to usual care (UC). Methods In a clinic cluster-randomized control trial conducted in a healthcare system serving a largely rural population, we randomized 34 primary care clinic clusters (with three clinics sharing clinicians randomized together) to: CDS; CDS+SDMT; UC. The sample included young adults aged 18–26 due for HPV vaccination with a study index visit from 08/01/2018–03/15/2019 in a study clinic. Generalized linear mixed models tested differences in HPV vaccination status 12 months after index visits by study arm. Results Among 10,253 patients, 6,876 (65.2%) were due for HPV vaccination, and 5,054 met study eligibility criteria. In adjusted analyses, the HPV vaccination series was completed by 12 months in 2.3% (95% CI: 1.6%–3.2%) of CDS, 1.6% (95% CI: 1.1%–2.3%) of CDS+SDMT, and 2.2% (95% CI: 1.6%–3.0%) of UC patients, and at least one HPV vaccine was received by 12 months in 13.1% (95% CI: 10.6%–16.1%) of CDS, 9.2% (95% CI: 7.3%–11.6%) of CDS+SDMT, and 11.2% (95% CI: 9.1%–13.7%) of UC patients. Differences were not significant between arms. Females, those with prior HPV vaccinations, and those seen at urban clinics had significantly higher odds of HPV vaccination in adjusted models. Discussion CDS may require optimization for young adults to significantly impact HPV vaccination. Trial Registration clinicaltrials.gov NCT02986230, 12/6/2016.